Highlights of the Bullionist controversy - David Laidler (The University of Western Ontario, Department of Economics, 2000)
This paper surveys the literature of the Bullionist controversy which dominated the development of Classical monetary economics between 1797 and the early 1820s. It highlights the contributions of Henry Thornton to the early phase of the debate, particularly his refutation of the Real Bill doctrine, and of David Ricardo to its later phases. The role of the Real Bills doctrine in the evidence given by directors of the Bank of England to the Bullion Committee of 1810 is also analysed. Ricardo's subsequent work on the resumption of convertibility, and the dissenting, sometimes inflationist, opinions of Thomas Attwood and the Birmingham School are then discussed. The paper ends with a brief account of how the Bullionist controversy influenced the later development of classical monetary economics in the 19th century.
Keywords: 330; Merkantilismus; Geldpolitik; Wechselkurssystem; Papierwährung; Großbritannien